Toxic bloom of Pseudo-nitzschia cuspidata (Bacillariophyceae) and domoic acid contamination of bivalve molluscs in Malaysia Borneo - Teng, Sing Tung; Abdullah, Nursyahida; Hanifah, Afiqah Halmiton; Tan, Suh Nih; Gao, Chunlei; Law, Ing Kuo; Leaw, Chui Pin; Lim, Po Teen (Elsevier, 2021)
In March 2018, an algal bloom of Pseudo-nitzschia was detected, for the first time, in a semi-enclosed lagoon in Miri, Sarawak, Malaysia Borneo. The plankton samples were collected for cell enumeration and species identification by electron microscopy and molecular characterization. Liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) was performed to detect and quantify the neurotoxin domoic acid (DA) in both the plankton and shellfish samples. The abundance of Pseudo-nitzschia cells ranged from 5.6Â ÃÂ 105 to 3.5Â ÃÂ 106Â cell L-1 during the bloom event. Morphological observation of the cells by transmission electron microscopy showed that the plankton samples comprised a single Pseudo-nitzschia morphotype resembling P. cuspidata. The ITS2 sequence-structure phylogenetic inference further supported the species identity as Pseudo-nitzschia cuspidata. Low levels of DA were detected in the plankton samples, with cellular DA, particulate DA, and dissolved DA of 257â504Â fg DA cell-1, 676Â ng L-1, and 15Â ng L-1, respectively. The amount of DA, 8Â Î¼gÂ g-1 tissue, was found present in the shellfish sample (Magallana sp.) which is below the regulatory limit of 20Â Î¼g DA g-1 tissue. The study documented, for the first time, DA contamination in shellfish that associated with bloom of P. cuspidata in the Western Pacific region.